Audit of Information Technology using ITIL V.3 Domain Service Operation on Communications and Information Technology Agency - Wijaya, Ari Putra; Widiadnyana, Putu; Swamardika, Ida Bagus Alit (International Journal of Engineering and Emerging Technology; Vol 1 No 1 (2016): July - December, 2017)
Good governance (good governance) is the most prominent issue in the management of public administration today, the municipal government of Denpasar appointed Office of Communications and Information Technology as a service manager SIPKD. The rapid development of the growing information demands to the use of information technology in the management of IT services that are strategic in getting the information service that is fast, precise and accurate. Hence the need for a standard integrated IT governance while providing best practice guidance in managing IT services framework. ITIL V3 is able to provide a detailed description of some IT practices with emphasis on life cycle management services relating to several areas of work which includes Service Strategy, Service Transition, Service Operation and CSI. Audit V.3 ITIL-based information technology is expected to give a picture of the extent to which the maturity level of the service rendered, resulting in a decision in the form of recommendations to management in Diskominfo Denpasar